Atlas of European millipedes 3: Order Chordeumatida (Class Diplopoda) - Kime, Richard Desmond; Enghoff, Henrik (European Journal of Taxonomy, 2021)
For each of the 534 species of the millipede order Chordeumatida known from Europe, available information on taxonomy, distribution and habitat is summarized, and the distribution in 50 × 50 km UTM/MGRS squares is shown on a map. Comparisons between Chordeumatida and the equally-sized order Julida are made with respect to distribution patterns and history of exploration.